Tangible tabletops: practical experiment and considerations for a design framework - da Costa, Vinicius Kruger; Zen, Eliana; de Oliveira, Jéssica Oliveira; Tavares, Tatiana Aires (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Research involving tangible interaction has been a productive area of study for decades but still faces significant challenges, such as the connection between the virtual and the physical, the lack of standard input/output devices, portability and interchangeability, and the complexity of continuous distributed interaction. In this sense, tangible tabletops emerge as the most used device in the development of applications and research related to this type of interaction, as they precisely can overcome many of the implementation barriers presented, in addition to offering benefits such as stimulating shared/social interaction and physicality. Several frameworks generate conceptual theoretical support for the functioning of the interaction, but they do not detail the practical characteristics of interaction with the tangible tabletop, nor do they discuss these in depth. The objective of this article is to present the development of a practical qualitative-quantitative experiment with tangible tabletop, discussing all the elements and characteristics involved in the interaction process. The results point to a series of limitations and potential uses of this device, and these considerations can generate inputs for the construction of a future project framework for interaction design.